Ethosomal (−)-epigallocatechin-3-gallate as a novel approach to enhance antioxidant, anti-collagenase and anti-elastase effects - Yücel, Çiğdem; Şeker Karatoprak, Gökçe; Yalçıntaş, Sena; Eren Böncü, Tuğba (Beilstein Journal of Nanotechnology, 2022)
Controlled release systems containing natural compounds have been successfully applied in cosmetics as antiaging products to enhance the penetration of active compounds through the skin. In this study, we aimed to develop novel ethosomal formulations containing a potent antioxidant, epigallocatechin-3-gallate (EGCG), and to evaluate their potential for use in cosmetics by determining their antioxidant and antiaging effects. Ethosomes (ETHs) were prepared via mechanical dispersion and characterized in vitro in terms of particle size (PS), zeta potential (ZP), polydispersity index (PDI), encapsulation efficiency percentage (EE%), and in vitro release. The best ETH formulation was used to prepare the ethosome-based gel (ETHG) by using Carbopol 980 as a gelling agent at a ratio of 1:1 (v/v). The gel formulation was evaluated regarding organoleptic properties, pH values, and viscosity. Stability studies were conducted for three months and changes in characterization parameters and residual EGCG content of ETHs were examined. Besides, for ETHG, organoleptic properties, pH values (every two weeks), and viscosity (first and twelfth week) were determined for three months. The 3-(4,5-dimethyldiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was used to test the cytotoxicity of the formulations and different EGCG solutions on the L929 cell line. The cell permeation properties and inhibitory effects of ETHs and ETHGs on collagenase and elastase enzymes were investigated compared to those of the solution form. Within the scope of antioxidant activity studies, 2,2-diphenyl-1-picrylhydrazyl (DPPH•) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS+•) radical scavenging and β-carotene/linoleic acid co-oxidation inhibitory effects were carried out. The optimized EGCG-loaded ETHs (F3) were within the nanoscale range (238 ± 1.10 nm). The highest encapsulation efficiency and in vitro release values were 51.7 ± 1.15% and 50.8 ± 1.70%, respectively. The ETHG was successfully formulated with F3-coded ETHs and the cytotoxicity test revealed that the formulations and the EGCG solution at different concentrations were nontoxic. In terms of cell permeability, enzyme inhibition, and antioxidant activity, the ethosomal formulations yielded better results compared to the EGCG solution. It was observed that the formulations had a long-term effect due to the stability of EGCG. The findings of the study underline the potential of antioxidant and antiaging effects of the developed ethosomal formulations for use in the cosmetic field.
Keywords: antioxidant effect; antiaging effect; epigallocatechin gallate; ethosomal gel; ethosome